Parasites in Arapaima gigas from the Peruvian Amazon by age group - Serrano-Martínez, Enrique (2015)
This study was carried out in 120 paiches (Arapaima gigas) distributed in four age groups (10 to 30, 31 to 180, 181 to 365 days and >1 year of age) from fish farms in the Peruvian Amazon to determine the prevalence and the affected organs. Eight parasite species are reported: monogeneans (Dawestrema cycloancistrium and D. cycloancistrioides), digeneans (Caballerotrema brasiliense), protozoa (Piscinodinium pillulare, Ichthyophthirius multifiliis and Trichodina sp), cestodes (Schizochoerus liguloides), and nematodes (Nilonema senticosum). The prevalence of parasitism was 0, 66.7, 90.0 and 66.7% for the age groups 10-30, 31-180, 181-365 days and >1 year of age, respectively.